2008
DOI: 10.1073/pnas.0711949105
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial addiction module toxin Doc inhibits translation elongation through its association with the 30S ribosomal subunit

Abstract: Bacterial toxin-antitoxin (TA) systems (or ''addiction modules'') typically facilitate cell survival during intervals of stress by inducing a state of reversible growth arrest. However, upon prolonged stress, TA toxin action leads to cell death. TA systems have also been implicated in several clinically important phenomena: biofilm formation, bacterial persistence during antibiotic treatment, and bacterial pathogenesis. TA systems harbored by pathogens also serve as attractive antibiotic targets. To date, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
104
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 55 publications
1
104
0
Order By: Relevance
“…Doc Induces RelE-mediated Cleavage of Model mRNAs-A recent study showed that Doc expression in E. coli strain BL21(DE3) led to mRNA stabilization (13). By contrast, we observe destabilization of two different model mRNAs (lpp and dksA) after induction of doc in E. coli strain MG1655 (Fig.…”
Section: Doc Induces Growth Arrest But Not Cell Death-induction Of Domentioning
confidence: 58%
See 1 more Smart Citation
“…Doc Induces RelE-mediated Cleavage of Model mRNAs-A recent study showed that Doc expression in E. coli strain BL21(DE3) led to mRNA stabilization (13). By contrast, we observe destabilization of two different model mRNAs (lpp and dksA) after induction of doc in E. coli strain MG1655 (Fig.…”
Section: Doc Induces Growth Arrest But Not Cell Death-induction Of Domentioning
confidence: 58%
“…Doc is an inhibitor of translation elongation through its association with the 30 S ribosomal subunit in a way similar to the antibiotic hygromycin (13). The action of Doc is suppressed by the antitoxin Phd, which consists of two domains.…”
mentioning
confidence: 99%
“…Doc P1 has been shown to interact with the 30S ribosomal subunit, and its toxicity is the result of inhibition of translation elongation, possibly at the translocation step (57). The Doc SI toxin shares 30% identity to Doc P1 , while the Phd SI is only distantly related to Phd P1 (17% identity), and they are even further less related to the Y. pestis proteins, 21% and Ͻ10%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced expression of the putative antitoxin homologues YefM and RelB also corroborates reduced cell growth. Both antitoxins participate in growth arrest and enable cell survival for prolonged times during environmental stresses (Liu et al, 2008). Antitoxins have been associated with cell persistence and are transcriptional repressors of toxin biosynthesis genes.…”
Section: Discussionmentioning
confidence: 99%